Üsküdar Kadılığı 335 numaralı Şer’ iyye Sicili Defteri (1118- 1119/ 1707) - Ertaş, M. Yaşar (My University, 1994)
unknown
Keywords: Ekonomi_Tarih_Osmalı İmparatorluğu; Marmara Bölgesi; Şer’iyye Sicilleri_Üsküdar; Tarih; Türkiye